Efektivitas Model Project Based Learning (PjBL) Berbantuan Media Riri Cerita Anak Interaktif terhadap Pemahaman Unsur Intrinsik Cerita - Sarah Aulia Ibrahim; Arifin Ahmad; Yuni Indriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study was motivated by the low Indonesian language learning outcomes of fifth-grade students at SDN Jatisari. The study aimed to determine the effectiveness of the Project-Based Learning (PjBL) model, supported by the